Perancangan Tata Letak Hasil Produksi Buis Berdasarkan ARC - Ernita; Verra Syahmer; Boby Rachman (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2018)
The layout of the facilities which is good and in accordance with the state of the company is one factor for the orderly and efficient arrangement of all facilities. The current problems that encountered in Yalesvava CV is the result of the production being constrained in the placement of the layout where the results of the resulting production due to sequence of irregular processes thereby resulting in accumulation of products that result in irregularity. Therefore, it is necessary to arrange the layout of production facilities in order to design buis layout based on ARC understanding and layout design layout design model from ARC understanding. Based on the background, the research objectives are: to produce layout design based on ARC understanding and layout design from ARC understanding. The result of this research is the finding that there are some work areas that must be moved or not moved and the discovery of the work area which is not appropriate in case it is make difficult to access. The advice given to CV. Yalesvava is maintaining the layout of raw material area so that it is not disturb the existing work access, to place the production result according to the product made by grouping the buis size, the printing can be done directly according to the specified size.